The Registry on Adverse Reactions of the American Medical Association - De Nosaquo, Norman (Methods of Information in Medicine, 1965)
The events which led to the development by the American Medical Association of an overall Registry on Adverse Reactions are described. The methods of operation involving reporting, collating, and disseminating information on adverse reactions to drugs and chemicals are outlined. A chart showing the organizational relationship of the Registry to the Council on Drugs is given. Copies of the report form, the guide for reporting, the code sheet, and the coding guide are presented. The author recommends that similar activities be undertaken in order to facilitate a free exchange of information throughout the world.